Factors that motivate university malaysia kelantan's students to participate in cultural tourism activities. - Azrin Aina Mohamad Zahari; Arfah Atira Abd Rahim; Che Ku Norfarizatul Che Ku Abdulah; Baoyee A/L Amran (2023)
A study to identify factors that encourage University Malaysia Kelantan students to participate in cultural tourism activities. A better understanding of this topic is to find the truth as far as the factors that are likely to encourage student involvement in participating in cultural activities. Also, this research is to investigate what draws students from University Malaysia Kelantan to engage in cultural tourism. Study participants were college students interested in learning more about the potential, benefits, and impact of cultural tourism activities for themselves. This research is to compare student motivation at the university's three different campuses (Jeli, Kota, and Bachok). Students at the University of Malaysia Kelantan will be polled using a questionnaire, followed by data analysis and study-related issues. The results of the study found that student involvement was driven by motivation, education, and the influence of friends to experience the experience of participating in cultural tourism activities. The result of this work helps and persuades the situation in attracting students' interest in participating in cultural activities among the students of University Malaysia Kelantan.